Ignaure: gender and genre - Marnette, S (Society for the Study of Mediaeval Languages and Literature, 2022)
This article examines an early-thirteenth-century short verse narrative that calls itself a lay but contains features that strongly remind us of fabliaux, mainly the use of uncouth elements and/or the ridiculing of some characters, despite its courtly setting. A close linguistic and narratological analysis of the text will explore how the narrator’s framing and reporting of his characters’ gendered discourses can both help and hinder the listener-readers to adjust their horizons d’attente with regard to this rather atypical narrative, thereby interweaving the notions of gender and genre.